Customer switching behaviour and subscriber growth in the Mobile Telecom Industry: A Case of Kasapa Telecom Ltd-Kumasi - Nyanteh, Alex Osei Opare (2014)
A thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration